Corporate restructuring in Japan: Who monitors the monitor? - Inoue, Kotaro; Kato, Hideaki Kiyoshi; Bremer, Marc (Journal of Banking & Finance, 2008)
Peek and Rosengren [Peek, J., Rosengren, E., 2005. Unnatural selection: Perverse incentives and the misallocation of credit in Japan. American Economic Review 95, 1144–1166] showed that, when the bubble economy era ended, regulatory forbearance and perverse incentives allowed Japanese banks to engage extensively in evergreening. This is the first comprehensive study to empirically analyze the economics of private debt restructurings of financially distressed companies in Japan, where the corporate monitoring mechanism is not market based but large-stakeholder based – typically, banks and affiliated companies. These stakeholders are expected to efficiently resolve potential bankruptcy or collapse with better information resulting from long-term relationships with the distressed firms. Our study, however, finds that private restructurings led by them failed because of delays in implementing fundamental solutions. Forbearance in addressing the needs of distressed firms demonstrates the weakness of such stakeholders in instituting discipline, hence the need for a system to “monitor the monitor”.